THE DEVELOPMENT OF DONATED BREAST MILK BANKS IN RUSSIA: NECESSITY AND POSSIBILITIES. SURVEY RESULTS WITHIN THE PILOT PROJECT OF A DONATED BREAST MILK BANK POWERED BY THE FEDERAL STATE BUDGETARY SCIENTIFIC INSTITUTION «SCIENTIFIC CENTRE OF CHILDREN'S HEAL - O. L. Lukoyanova; T. E. Borovik; I. A. Belyaeva; L. S. Namazova-Baranova; G. V. Yatsyk; E. P. Bombardirova; V. A. Skvortsova; E. V. Shchepkina ("Paediatrician" Publishers LLC, 2015)
A child should receive the donated breast milk when a mother cannot provide it. The United Association of Perinatal Care resolution underlines that the creation of donated breast milk banks pursuits the national policy for the support and popularization of breast feeding. The article presents the results of survey among mothers, fathers and medical workers regarding necessity and possibility of developing donated breast milk banks in Russia. The respondents showed low awareness of the benefits and safety of the donor breast milk for children with deficiency or lack of the mother's milk. Received data points out the necessity of promotion of donated breast milk banks in order to stimulate breast feeding as well as to raise the awareness of breast feeding necessity.